Evaluasi Program Pendidikan Keaksaraan di PKBM Bina Cipta Ujung Berung - Malnava Sari, Iis; Wahyudin, Uyu (Jurnal Empowerment, 2025)
There are still many issues with Indonesia's educational system, such as underprivileged individuals who are illiterate. According to information from the Ministry of Education and Culture, 6,007,486 persons in Indonesia were illiterate in 2014. By taking a closer look at these issues, the community has stepped up the execution of literacy instruction initiatives in an effort to raise Indonesia's literacy level. PKBM Bina Cipta Ujung Berung is one of the non-formal educational institutions that administers this pre-literacy education program. The CIPP approach is the one applied in this evaluation. The findings demonstrate that the language used in the current literacy education program at PKBM Bina Cipta Ujung Berung has considered the specific needs of pupils in the region who are trying to overcome social and economic issues that exist in society. In addition, PKBM Bina Cipta Ujung Berung also has sufficient resources to support literacy education programs and the process of implementing literacy education programs at PKBM Bina Cipta Ujung Berung is going very well with results that can be seen from the increased level of students' literacy. the long-term impact on this program needs to be continuously monitored and evaluated to ensure the sustainability of the results achieved. Keywords: Evaluation, Program, Education, Literacy